13 Improving patient flow and experience of cardiovascular computed tomography (CCT) at bart's heart centre. (May 2018) - Tanna, Reena; Patel, Ketna; Maxwell, Jenny; Yap-Sanderson, Jo; Castle, Emily; Balan, Anu; Davies, Ceri; Cheasty, Emma
Abstract : Introduction: Approximately 21–23 computed tomography coronary angiograms (CTCAs) are performed daily at Bart's Heart Centre, amongst the largest performed per year in the UK. This is one of only two regions in the UK performing near the projected numbers required for successful implementation of the recent 'Chest pain of acute onset' guidelines. A significant increase in demand of current resources is likely. Subjectively, patient flow through the cardiovascular CT department is already contributing to sub-optimal staff and patient satisfaction. Our aim was to ensure that 95% of all patients undergoing CTCA at Bart's Heart Centre would be scanned and discharged within 60 min of their appointment time by December 2017. Methods: We undertook initial process mapping to understand the existing patient pathway following thier arrival in the department. We constructed a driver diagram to identify primary and secondary drivers and generate change ideas. We completed two plan-do-study-act (PDSA) cycles thus far: PDSA#1 – Clinician assistance with patient preparation; PDSA#2 – Post-scan observation time reduced from 30 min to 15 min in keeping with guidelines for standard practice. Results: At baseline 43% of patients were scanned and discharged within 60 min. Following the first change this increased to 81% and after second change to 89%. Baseline median time in department was 71 min, which fell to 47.5 min after the first change with a further fall to 45 min after the second change. Both change ideas have subsequently been adopted in to routine clinical practice. Conclusion: We demonstrated successful implementation of two changes in practice which have improved patient flow through the CCT department. Our aim is to identify further areas of improvement to better our patient flow through the department, and maintain high scanning numbers to meet proposed guidelines.